Study on Application of Model Based 3D Process Planning System. Issue 2 (April 2021) - Yin, Haijun; Qiao, Xinghua; An, Weixing
Abstract: based on the study on existing status of MBD technology applied in design and manufacturing aspects, this article analyzes the importance of model-based 3D process planning system utilized in manufacturing sector, puts forward a package of MBPP application proposal and describes the application objectives, application structure, implementation process and major functions. The model based MBPP system is developed based on process planning proposal, and has been validated by its application in the development and manufacturing of model X aircraft.